Timing and duration of phenological sequences of alpine plants along an elevation gradient on the Tibetan plateau - Wang, Shiping; Wang, Changshun; Duan, Jichuang; Zhu, Xiaoxue; Xu, Guangping; Luo, Caiyun; Zhang, Zhenhua; Meng, Fandong; Li, Yingnian; Du, Mingyuan (Agricultural and forest meteorology, 2014)
•Timing of phenological events is not necessarily delayed as elevation increases.•Changes in timing of phenological events are inconsistent as elevation increases.•Individual reproductive components have independent responses to climate change.•Duration of reproduction stage is dependent on timing of phenological events.•Response of phenological events to climate change is species-specific. Previous studies have focused on the effects of increased temperatures on a single green-up and/or flowering event, but less is known about how acceleration of spring phenology may change subsequent phenological events. We present results of a field experiment to test the hypotheses that (1) the timing of phenological events does not necessarily delay as elevation increases; (2) changes in the timing of a sequence of phenological events will be consistent for all phenological events along the elevation gradient; and thus (3) change in the timing of phenological events does not affect the duration of the entire reproductive stage in the alpine region. The experiment was conducted along an elevation gradient from 3200 to 3800m using two early-spring flowering (ESF) sedges and four mid-summer flowering (MSF) plants (two forbs and two grasses). Generally, our results only supported the first hypothesis. Lower elevation delayed the starting dates of all phenological events for ESF plants at 3200m compared with other elevations, whereas the opposite trend was observed for MSF-grasses. MSF-forbs had the earliest leaf-out at 3200m and the earliest first flowering at 3600m, and onset of fruit-set advanced with increasing elevation. The entire reproductive duration was shortened with increasing elevation for MSF-forbs, whereas it was the shortest for ESF at 3600m and for MSF-grasses at 3200 and/or 3800m. Individual reproductive stages had independent responses to climate change. The duration of the entire growing season for ESF plants decreased as elevation increased. For MSF-forbs, it was longest at 3200m and shortest at 3400m, while for MSF-grasses it was shortest at 3200m and at 3800m. Reproduction was compressed into shorter time periods only for MSF-forbs at 3600 and 3800m. Therefore, reproduction is not tightly integrated across the life cycle, and earlier reproductive development induced by warmer spring temperatures did not consistently advance flowering and fruiting times and their durations for the alpine plants studied. The effects of climate change on the timing and duration of phenological events were species-specific. Selection for changes in the timing and duration of individual phenological stages in response to climate change due to evolutionary adaptation should be taken into account.